2017
DOI: 10.3390/agriculture8010001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mesotrione Leaching Applied Alone and Mixed in Seven Tropical Soils Columns under Laboratory Conditions

Abstract: Herbicide leaching is influenced by soil physical and chemical properties as well as the prevailing climatic conditions. However, little is known about leaching of mixture of herbicides in the soil, especially in tropical regions like Brazil. The objective of this study is to evaluate the leaching of 14 C-mesotrione (cyclohexane-2-14 C-mesotrione) alone and in a mixture with S-metolachlor and terbuthylazine in seven tropical soil columns under laboratory conditions. These soils represented a wide range of prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Regarding herbicide mixtures, Refatti et al [66] determined the leaching potential of herbicides used in the Clearfield® system for irrigated rice and concluded that mixtures of imazethapyr + imazapic, imazapyr + imazapic, and imazethapyr leached into the soil, reaching depths of up to 25 cm in floodplain soil. However, in a study conducted by Mendes et al [67], the application of mesotrione, alone or in a mixture with S-metolachlor and terbuthylazine, did not influence the leaching of this herbicide.…”
Section: Leachingmentioning
confidence: 82%
“…Regarding herbicide mixtures, Refatti et al [66] determined the leaching potential of herbicides used in the Clearfield® system for irrigated rice and concluded that mixtures of imazethapyr + imazapic, imazapyr + imazapic, and imazethapyr leached into the soil, reaching depths of up to 25 cm in floodplain soil. However, in a study conducted by Mendes et al [67], the application of mesotrione, alone or in a mixture with S-metolachlor and terbuthylazine, did not influence the leaching of this herbicide.…”
Section: Leachingmentioning
confidence: 82%
“…However, the study on mesotrione leaching in soil of different texture (clay, loam, sandy loam and sandy soils; pH 6.4-7.2) showed low mobility of the herbicide applied to corn field at 150 g ai ha -1 (residues were mainly found in soil up to 10 cm at levels in range 6-13 μg kg -1 1 mo after the corn harvest) (Rouchaud et al, 2001). In contrast, mesotrione was detected up to 30 cm of tropical soil layer and its leaching was higher in more alkaline soils with low values of cation exchange capacity (CEC) and OC/clay content (Mendes et al, 2018). Barchanska et al (2012) indicated that mesotrione is easily degradable and can be eluted from soil with a heavy rainfall (47 mm m -2 ) making the residues detectable in soil only 1 wk after its application at a recommended rate.…”
Section: Resultsmentioning
confidence: 99%